PECHA KUCHA – FORMAT JAPONEZ DE PREZENTĂRI - PÂNZARU, Ludmila (BIBLIOPOLIS, 2020)
The article is about a revolutionary format of presentation implemented in 2003 in Tokyo, by two architectures Astrid Klein and Mark Dytham, and extended in the world. The article offers information related to the steps of preparing this type of presentation.